Synthesis and Thermal Stability of Cassava Starch-Grafted Polyacrylamide Hydrogel by Microwave-Assisted Method - Maudy Pratiwi Novia Matovanni; Sperisa Distantina; Mujtahid Kaavessina (CHEMICA: Jurnal Teknik Kimia, 2023)
Cassava starch-grafted polyacrylamide (CSt-g-PAM) hydrogels were generated by grafting cassava starch as the backbone, acrylamide as the monomer, and potassium peroxodisulfate as the initiator. In this work, we investigated the effect of monomer concentration and irradiation time on the thermal stability of CSt-g-PAM.  Cassava starch, acrylamide, and KPS were added to the distilled water, and microwaves were used to help with grafting. The grafting process was carried out using an irradiation-cooling cycle. The cycle was repeated until a gel was formed for 180 seconds (6 cycles). The gel formed was soaked in acetone until a precipitate formed. The precipitate obtained was dried in an oven at 50 ºC for 24 hours. The dried precipitated CSt-g-PAM was used in the characterization process. X-ray powder diffraction (XRD) was used to determine the crystalline structure of CSt-g-PAM. The thermogravimetric (TGA) study of CSt-g-PAM revealed its thermal stability. The XRD spectra of  CSt-g-PAM revealed that the cassava starch backbone was effectively grafted with polyacrylamide. TGA showed that CSt-g-PAM has much higher thermal stability than native cassava starch. The greatest performance was obtained by preparing CSt-g-PAM with 10 g of acrylamide and 180 s irradiation time, as evidenced by the highest percentage of residual weight in the TGA findings. The thermal stability features of CSt-g-PAM make it interesting for use in EOR applications.